Potencial de leveduras Saccharomyces e não-Saccharomyces Autóctones do cerrado como culturas iniciadoras em processos de panificação - Condessa, Bárbara Marques Bianchini (Universidade Federal do Tocantins, 2020)
Bread was one of the first applications of fermentative processes in history. Despite the central role of baking yeast in the final product quality, research on the impact of unconventional microorganisms on the sensory complexity of bread is still scarce. Thus, the present study aims to contribute to recent investigations on the impact of wild and unconventional yeasts on the physicochemical parameters and aromatic profile of bread. For this, strains of wild Candida tropicalis and Saccharomyces cerevisiae, isolated from cerrado fruit and tree bark, respectively, were used. Static and bioreactor cultivation were analyzed by comparing growth kinetic parameters (specific velocity, generation time and cell productivity). Growth capacity in medium with high sugar concentration and resistance after lyophilization were analyzed. With the ready-made breads and having as control the bread made with commercial Saccharomyces cerevisiae yeast (Dona Benta), the main physicalchemical quality parameters of the bread (pH, humidity, specific volume, crust and crumb color) were compared. ), as well as the profile of volatile compounds in bread. Bioreactor cultivation was able to attenuate the lag phase of growth and halved yeast generation time. Yeasts showed growth capacity in medium containing high sugar concentration (115g / L), which is desirable for baking yeasts. The medium containing 10g / L maltose favored the growth of both yeasts. The bread produced with Candida tropicalis yeast (ART101.3) stood out for having the physical parameters closest to the control bread, namely: pH = 6.00 ± 0.11; specific volume of 2.33 ± 0.06ml / g and humidity of 27.06 ± 2.16%, plus the production capacity of volatile compounds other than control yeast such as benzyl alcohol, hexyl acetate, m-cymene, α- tujene, β-pinene and dodecane, producing breads with greater sensory complexity. Thus, the present work demonstrates the potential of native Cerrado yeasts to be used and exploited in industrial processes, as well as contributing to the diversification of bread starter cultures.